Ionospheric Perturbations Induced by a Very Severe Cyclonic Storm (VSCS): A Case Study of Phailin VSCS. Issue 1 (8th January 2020) - Dube, Adarsh; Singh, Rajesh; Maurya, Ajeet K.; Kumar, Sanjay; Sunil, P. S.; Singh, Abhay K.
Abstract: We investigate F region ionospheric perturbations associated with very severe cyclonic storm Phailin which occurred in Bay of Bengal during 09–12 October 2013. Very severe cyclonic storm Phailin was the most intense supercyclone over the Bay of Bengal with intensity T6.0. The primary data used are lightning data from Global Lightning Detection 360 network, Global Position System‐derived total electron content information from seven Global Position System stations located in the cyclone impact region, and meteorological data. This is the first report from north Indian Ocean which investigates the perturbations induced in the ionosphere associated with a cyclone. Investigation of lightning discharges occurrence at the storm center along the cyclone track line showed that the lightning growth pattern closely follows the cyclone intensity during the initial, mature, and decay stages. The total electron content computed from seven Global Position System stations showed that differential total electron content is enhanced during very severe cyclonic storm days, compared with precyclone and postcyclone days. The maximum peak‐to‐peak perturbation in differential total electron content values at Port Blair located at Andaman‐Nicobar Islands in Bay of Bengal was 0.33 TECu during the cyclone days, whereas it was only 0.11 TECu during the no‐cyclone days. The results show that most probably gravity waves generated from cyclonic thunderstorms can couple with the upper atmosphere and modify the dynamics of the ionosphere. Tropical cyclones and large thunderstorms are an important source from below which couple with ionosphere and manifest in the form of ionospheric perturbations. Key Points: First study from north Indian Ocean which concentrates on ionospheric perturbations associated with a very severe cyclonic storm (VSCS) Study uses TEC data from seven GPS station located in the impact region of VSCS Phailin which occurred during 09–13 October 2013 Peak perturbation in DTEC at GPS stations is found to be maximum during VSCS in comparison with precyclone and postcyclone days